Policing in the Shadows: Undercover Buying and the Social Construction of Legal Evidence in Indonesia’s Post-KUHAP 2025 Criminal Justice System - Tubagus Heru Dharma Wijaya; Abdul Madjid; Setiawan Noerdajasakti; Lucky Endrawati (Baileo: Jurnal Sosial Humaniora, 2026)
This study examines the sociological dynamics of undercover buying in Indonesia’s post–Criminal Procedure Code 2025 (KUHAP 2025) criminal justice system, focusing on the social construction of legal evidence through investigative practices. It addresses the tension between effective narcotics enforcement and the obligation to uphold due process and human rights. Moving beyond a purely normative legal perspective, the study analyzes how undercover buying operates as a social practice that shapes the production, interpretation, and legitimacy of evidence. A qualitative socio-legal approach is employed, integrating normative analysis of statutory frameworks with empirical data. Data are drawn from court decisions, legal documents, and case reports, complemented by in-depth interviews with law enforcement officers, prosecutors, and legal practitioners. Analysis is conducted interpretatively using a social construction framework to examine how evidence is produced and legitimized within institutional settings. The findings indicate that evidence derived from undercover buying is not inherently objective but emerges from interactions among investigators, suspects, and legal norms. The practice may blur the boundary between enforcement and the construction of criminal acts, particularly where entrapment or excessive intervention occurs. Despite strengthened procedural legality under KUHAP 2025, a gap remains between legal norms and implementation. This study offers novelty by conceptualizing undercover buying as a socio-legal practice that constructs legal reality. It contributes to Global South sociology of law and recommends clearer operational standards and community-based oversight to ensure accountable and rights-based criminal justice.